Kayak Girl - Devine, Monica (Book collections on Project MUSE., 2012)
In Kayak Girl, a young child learns to cope with serious loss by focusing on something larger than herself. After her mother dies, Jana becomes withdrawn. Her grandfather, a carver, pays the girl a visit and finds her unresponsive to his care. He carves a figure of a girl in a kayak and asks Jana to promise that she will watch for the figure after he releases it upriver. Through the following seasons, Jana goes to the river daily and finds strength in the positive memories from her short time with her mother, even as she imagines the distant kayak girl's struggles. Eventually, they are reunited, and Jana's spirit is revived. Throughout the book, watercolor illustrations take readers to a magical place along an Alaska river and demonstrate the power of memory and a sense of place in the natural world.